The effects of the association of placenta previa and placenta accreta on the short-term maternal morbidity - Gezer, Şener; Türe, Mehmet Zeki; Balcı, Sibel; Yücesoy, İzzet (Perinatal Journal, 2020)
Objective: We aimed to compare the effects of placenta previa (PP) and placenta accreta (PA) on the short-term maternal morbidity alone and together. Methods: The data of the patients who were diagnosed with PP, PA or placenta previa accreta (PPA) which includes both of them between January 2010 and December 2018 in a tertiary reference center were analyzed retrospectively. The records of the patients were compared between 3 groups for age, gravida, parity, week of gestation, previous cesarean section, history of curettage and myomectomy, gestational complications, placental location, hospitalization at hospital and intensive care unit, decreased level of hemoglobin, blood product transfusions, procedures to control bleeding and complications. Results: Six out of 192 patients were excluded from the study as they delivered in other hospitals, and the data of 186 patients were analyzed. There were 141 (75.8%) patients with PP only, 9 (4.8%) patients with PA only, and 36 (19.4%) patients with PPA. The erythrocyte transfusion was significantly higher in PPA patients than PP patients (p<0.001). The possibility for the transfusion of any blood product was lower in PP group than other groups. While the rate of hospitalization at intensive care unit was higher in PPA group, the number of hospitalization day at hospital was significantly lower in PP group than PA (p=0.042) and PPA (p<0.001) groups. Urinary complication was observed less in PP patients. The hysterectomy rate was higher in PPA patients with than PP and PA patients (p=0.004). Conclusion: The rates of maternal morbidity and hysterectomy increase when PP and PA are together compared to the cases where they are alone.